A theology of Revelation God's grand plan to defeat evil, rescue his people, and transform his creation - Duvall, J. Scott; Köstenberger, Andreas J. 1957- (Grand Rapids, Michigan Zondervan Academic, 2025)
"A Theology of Revelation by J. Scott Duvall in Zondervan's Biblical Theology of the New Testament series provides a comprehensive look at the theology of John's Apocalypse. One of only a few dedicated theologies of Revelation, Duvall's book leaves no stone unturned in the study of the final book of the Christian canon of Scripture"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Theology